Experimental study on the mechanical properties of C30 molybdenum tailings concrete after high-temperature and sulfate corrosion - Bing Xie; Jian Yuan; Cheng-Jin Jiang (Heliyon)
In order to study the durability of molybdenum tailings concrete after a specific period of wet-dry cycle tests and exposure to high temperatures, this paper investigates the rule of change of the mechanical properties of molybdenum tailings concrete under the coupled influence of sulfate corrosion and high-temperature environmental conditions. A total of five C30 concrete prisms with molybdenum tailings content (0 %, 25 %, 50 %, 75 %, and 100 %) were considered in the tests, with sulfate solution concentrations of 0 g/L, 20 g/L, and 50 g/L, and exposure temperatures of 25° at room temperature and 400° at high temperature, respectively. The test results showed that the mass loss rate of concrete prisms with different molybdenum tailings substitution rates under sulfate corrosion and high temperature environment showed an increasing and then decreasing trend. The specimens with 25 % molybdenum tailings content still maintain high mechanical properties after wet-dry cycle tests of sulfate solution and high temperature, and the reduction of peak stress in this group is only 11 %, and the reduction of elastic modulus is 1 %; the rest of the molybdenum tailings content has a reduction of peak stress of about 25 %, and the reduction of modulus of elasticity is more than 10 %. The plastic deformation capacity of molybdenum tailings concrete decreases under the single-factor effects of wet-dry cycle tests of sulfate solution and high temperature effects, but the plastic deformability capacity of the specimens is enhanced under the combined effects of multiple factors. The stress-strain curve formulas for molybdenum tailings concrete under high temperature, wet-dry cycle tests of sulfate solution, and coupled wet-dry cycle tests of sulfate solution and high temperature were fitted. The results of this study can provide experimental data and valuable references for the engineering application of molybdenum tailings concrete under wet-dry cycle tests of sulfate solution and high temperature conditions, laying a foundation for further research.